Kajian Pelestarian Masjid Lama Gang Bengkok di Kota Medan Berbasis Nilai Historis, Arsitektural dan Sosial - Rulliansyah, Farhan Putra; Rani, Nandi; Nuraini, Cut; Andriana, Melly; Indira, Sri Shindi (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Masjid lama gang Bengkok is one of the historical heritage sites in Medan City, reflecting the integration of Malay and Chinese cultures within an Islamic context. Built around 1874 with the support of Tjong A Fie, a prominent Chinese figure during the Deli Sultanate era, the mosque features traditional Malay architectural styles with Chinese influences visible in its ornamentation and structural elements. Currently, the mosque’s physical condition is relatively well-preserved, but it faces environmental pressures from urban development and a lack of adequate historical interpretation systems. This study aims to identify the historical, architectural, and social values embodied in the mosque and to develop contextual preservation strategies. The research employs a qualitative approach through observation, literature review, and community interviews. The findings recommend community-based preservation, minor restoration, and the enhancement of historical narratives within public spaces.